Evaluation of the clientele's attitudes toward the utilization of media materials of the Quezon City Public Library - Carlos, Angeline F. (1994)
The Quezon City Public Library in East Avenue is a library known to have a good collections of print and nonprint materials. In this regard, a study is made to evaluate the collection and services of the above mentioned library.